2018
DOI: 10.32598/bcn.9.5.357
|View full text |Cite
|
Sign up to set email alerts
|

Research Paper: Chemical Composition and Role of Opioidergic System in Antinociceptive Effect of Ziziphora Clinopodioides Essential Oil

Abstract: Introduction:Ziziphora Clinopodioides has been used widely for various therapeutic purposes in Iranian folk medicine. The current study aimed to determine interaction of antinociceptive effect of the Essential Oil of Ziziphora Clinopodioides (EOZC) and opioidergic system in male rats using formalin test.Methods:Sixty-four male Wistar rats were divided into eight groups. The groups 1 to 7 were injected with normal saline, vehicle (Tween-80, 0.5%), 10, 20, 40 mg/kg of the EOZC, morphine (5 mg/kg) and naloxone (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Pain is formed in the second (inflammatory) phase when histamine, serotonin, bradykinin, and PGs are released in response to inflammation in the tissue wounded by formalin. Peripherally acting medications, such as anti-inflammatories ( Mohammadifard and Alimohammadi, 2018 ), are only efficacious in the second phase of the formalin test, whereas centrally acting pharmaceuticals, such as opioid analgesics, suppress both phases. In a dose-dependent way, we found that the tested samples of H. aitchisonii decreased the pain response to both phases of the formalin test, demonstrating an antinociceptive impact at both the central and peripheral levels.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is formed in the second (inflammatory) phase when histamine, serotonin, bradykinin, and PGs are released in response to inflammation in the tissue wounded by formalin. Peripherally acting medications, such as anti-inflammatories ( Mohammadifard and Alimohammadi, 2018 ), are only efficacious in the second phase of the formalin test, whereas centrally acting pharmaceuticals, such as opioid analgesics, suppress both phases. In a dose-dependent way, we found that the tested samples of H. aitchisonii decreased the pain response to both phases of the formalin test, demonstrating an antinociceptive impact at both the central and peripheral levels.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I consists of neurogenic nociception by direct stimulation of nociceptors via C fibers to the dorsal horn of the spinal cord after substance P is secreted and acts as a neurotransmitter. The second phase consists of inflammatory-induced pain due to the release of serotonin, histamine, bradykinin, and prostaglandins from formalin-damaged tissue [ 32 ]. The pain response in both phases is processed at the spinal level.…”
Section: Discussionmentioning
confidence: 99%
“…administration at a dosage of 10 mL/kg body weight. All the test doses of the drugs used in this study and drug administration schedules were determined based on the previous reports and the authors’ unpublished pilot studies [ 2 , 3 , 11 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pain arises as a result of an injurious stimulus either from the environment or within the body and is subsequently disseminated by the activation of nociceptors by inflammatory mediators. Then, these receptors convey the pertinent information via afferent fibers to the central nervous system (CNS) [ 3 ]. Recently, in light of the deleterious consequences caused by a multitude of synthetic analgesics, including non-steroidal anti-inflammatory drugs (NSAIDs) and opioids, there has been a growing demand for the discovery of innovative analgesic medications that offer improved effectiveness and safety.…”
Section: Introductionmentioning
confidence: 99%